2003
DOI: 10.1097/00004691-200307000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Disturbed Impulse Propagation in Multiple Sclerosis Identified by Low and High Frequency Somatosensory Evoked Potential Components

Abstract: In human median nerve somatosensory evoked potentials (SSEPs), high frequency (600 Hz) oscillations (HFOs) are superimposed onto the low frequency SSEP component N20. High frequency oscillations are generated both in deep axon segments of thalamo-cortical projection neurons and at the primary somatosensory cortex. The present study aimed to test the hypothesis that HFOs might be more sensitive to temporal dispersion caused by demyelinating lesions in multiple sclerosis (MS) than the N20. The authors recorded H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 28 publications
2
3
0
5
Order By: Relevance
“…In strong agreement are the repeated observations in humans of non-linear neural response interactions within the initial 100 ms post-stimulus onset (Giard and Peronnet, 1999;Foxe et al, 2000;Molholm et al, 2002;Lutkenhoner et al, 2002;Fort et al, 2002a,b;Gobbele et al, 2003; see also Murray et al, 2004Murray et al, , 2005aGonzalez Andino et al, 2005) and/or within brain regions traditionally held to be 'unisensory' in their function (e.g. Macaluso et al, 2002;Calvert, 2001;Murray et al, 2004Murray et al, , 2005aMartuzzi et al, 2007;Meylan and Murray, 2007; see also Ghazanfar et al, 2005;Kayser et al, 2005Kayser et al, , 2007 for recent functional evidence from non-human primates).…”
Section: Introductionsupporting
confidence: 60%
“…In strong agreement are the repeated observations in humans of non-linear neural response interactions within the initial 100 ms post-stimulus onset (Giard and Peronnet, 1999;Foxe et al, 2000;Molholm et al, 2002;Lutkenhoner et al, 2002;Fort et al, 2002a,b;Gobbele et al, 2003; see also Murray et al, 2004Murray et al, , 2005aGonzalez Andino et al, 2005) and/or within brain regions traditionally held to be 'unisensory' in their function (e.g. Macaluso et al, 2002;Calvert, 2001;Murray et al, 2004Murray et al, , 2005aMartuzzi et al, 2007;Meylan and Murray, 2007; see also Ghazanfar et al, 2005;Kayser et al, 2005Kayser et al, , 2007 for recent functional evidence from non-human primates).…”
Section: Introductionsupporting
confidence: 60%
“…In a recent study, it was found by analysis of recordings of somatosensory evoked potentials that the transmission of impulses generated by median nerve stimulation to S I was disturbed in MS patients (Gobbelé et al, 2003). Despite the reduced capacity of S I to process sensory stimuli, S I still retains its plasticity.…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…For instance, if recording of traveling potentials far from the axon, is desired, it will be important to keep low frequency (high pass) filters as low as possible. However, if the goal of an experiment is to analyze the changes in the local environment that a nerve impulse encounters, it is best to set the low frequency filter high enough to reduce the amplitude of the traveling potentials [30]. …”
Section: Discussionmentioning
confidence: 99%